In Vitro Cyto- and Genotoxicity Assessment of Antibacterial Paints with Triclosan and Isoborneol - Micaela Machado Querido; Fernanda Rosário; Maria João Bessa; Francisca Mendes; José Carlos Teixeira; João Paulo Teixeira; Cristiana Costa Pereira (Toxics, 2022)
Surfaces with antimicrobial properties are gaining notoriety as an efficient method to avoid surface contamination. Self-disinfecting paints are a promising strategy towards cleaner indoor environments by preventing the colonization of walls with microorganisms. However, its widespread use needs an appropriate toxicological safety evaluation due to the potential for biological disturbance associated to its biocidal activity. In this work, the cyto- and genotoxic assessment of two self-disinfecting paints containing the antimicrobial substances triclosan (TCS) and isoborneol (ISB) is performed. HaCaT and A549 cell lines models were selected for the in vitro assessment. To evaluate the cytotoxicity, tests by direct contact and on extracts obtained from leaching were performed following ISO 10993, whereas the genotoxicity was assessed by comet assay and cytokinesis-block micronucleus (CBMN) assay. The results showed low levels of cyto- and genotoxicity under the models and conditions tested, indicating that these substances have commercial potential.